HUBUNGAN PEKERJAAN, PENDIDIKAN IBU NIFAS TERHADAP SIKAP PEMBERIAN AIR SUSU IBU (ASI) DI PRAKTEK MANDIRI BIDAN NURYANTI - Lili Nurmaliza; Rhina Chairani Lubis; Muryani Muryani (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Breast milk is a natural food that contains nutrients needed by babies in the first six months. Breast milk can meet the nutritional needs of infants during the first year to the second year of life. Breastfeeding is the first immunization of children, providing protection from respiratory tract infections, diarrheal diseases, and other potentially life-threatening diseases. Breastfeeding also has a protective effect against obesity and non-communicable diseases. Objective: This study was to examine the relationship between employment, education of postpartum mothers on breastfeeding attitudes in the Independent Practice of Midwives Nuryanti in 2022. Methods: The research design was cross sectional with a population of all postpartum mothers who Maternity in the Independent Practice of Midwives Nuryanti with a sample of 45 people. Results: Analysis using the Square-Test, the results of the research that got a job, the education of postpartum mothers on breastfeeding attitudes with a value (p value = 0.000). Conclusion: where it can be concluded that there are the relationship between work, education of postpartum mothers on breastfeeding attitudes.